2010
DOI: 10.1152/physiolgenomics.00064.2010
|View full text |Cite
|
Sign up to set email alerts
|

Elevated myocardial Na+/H+exchanger isoform 1 activity elicits gene expression that leads to cardiac hypertrophy

Abstract: In myocardial disease, elevated expression and activity of Na+/H+ exchanger isoform 1 (NHE1) are detrimental. To better understand the involvement of NHE1, transgenic mice with elevated heart-specific NHE1 expression were studied. N-line mice expressed wild-type NHE1, and K-line mice expressed activated NHE1. Cardiac morphology, interstitial fibrosis, and cardiac function were examined by histological staining and echocardiography. Differences in gene expression between the N-line or K-line and nontransgenic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 58 publications
5
70
0
Order By: Relevance
“…Studies also showed that the inhibition of NHE1 by inhibitors attenuated the hypertrophy of cardiomyocytes (23)(24)(25)(26)(27). Because we also found a significant decrease in the medial wall thickness of pulmonary arteries in NHE1-deficient mice with decreased hypoxic pulmonary hypertension and vascular remodeling (11), we hypothesized that the effects of NHE1 on hypoxia-induced PASMC hypertrophy were also mediated via E2F1.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Studies also showed that the inhibition of NHE1 by inhibitors attenuated the hypertrophy of cardiomyocytes (23)(24)(25)(26)(27). Because we also found a significant decrease in the medial wall thickness of pulmonary arteries in NHE1-deficient mice with decreased hypoxic pulmonary hypertension and vascular remodeling (11), we hypothesized that the effects of NHE1 on hypoxia-induced PASMC hypertrophy were also mediated via E2F1.…”
mentioning
confidence: 74%
“…Studies indicated the relationship between NHE1 and myocardial hypertrophy, showing that the inhibition of NHE1 activity by inhibitors reduced cardiac hypertrophy in animals and cultured cardiomyocytes (23)(24)(25)(26)(27). The increased medial wall thickness of pulmonary arteries in pulmonary hypertension and vascular remodeling is involved not only in the proliferation of PASMCs, but also in the hypertrophy of PASMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NHE1 is also involved in cardiac hypertrophy and heart failure, as shown by studies in animal models and isolated cardiomyocytes (10,12,21,37,53). The expression level of NHE1 was reported to be elevated in various hypertrophic animal models (12,24).…”
mentioning
confidence: 98%
“…The link between NHE-1 and calcineurin activation is reinforced by a number of previous studies linking the inhibition of NHE-1 activity with prevention of calcineurin activation (Ennis et al, 2007;Kili c et al, 2010;Guo et al, 2011). Moreover, myocardial NHE-1 overexpression in mice in the absence of insult results in hypertrophy and left ventricular dysfunction (Nakamura et al, 2008;Xue et al, 2010). Nakamura and colleagues (2008) have linked this phenomenon to calcineurin activation as a direct consequence of NHE-1-dependent elevation in intracellular Ca 21 concentrations.…”
Section: Discussionmentioning
confidence: 94%
“…A particularly important response to an elevation in intracellular calcium concentrations, and the subsequent formation of the calciumcalmodulin complex, is activation of calcineurin, a calciumactivated phosphatase critically important for the hypertrophic program (Frey and Olson, 2003). Indeed, overexpression of cardiac NHE-1 in transgenic mice on its own, in the absence of pathologic insult, has been shown to induce calcineurin upregulation and a calcineurin-dependent hypertrophic response (Nakamura et al, 2008;Xue et al, 2010;Mraiche et al, 2011).…”
Section: Introductionmentioning
confidence: 99%